2021
DOI: 10.3390/healthcare9010041
|View full text |Cite
|
Sign up to set email alerts
|

Does the Type of Exposure to Workplace Violence Matter to Nurses’ Mental Health?

Abstract: Workplace violence is a prevalent phenomenon in healthcare, particularly among nursing professionals. Exposure to workplace violence may be direct through firsthand involvement, indirect through secondhand witnessing, or both. Even though implications for victims of workplace violence have been well-studied, less is known about the various types of exposure and their effects on nurse mental health. The purpose of this study is to examine the impact of workplace-violence exposure types on the mental health of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 49 publications
1
38
0
Order By: Relevance
“…This would signal that verbal abuse is not acceptable and mitigate a major precipitant of OD. The importance of tending to and supporting nurses' mental health cannot be understated (Havaei, 2021;Liu et al, 2020;WHO 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This would signal that verbal abuse is not acceptable and mitigate a major precipitant of OD. The importance of tending to and supporting nurses' mental health cannot be understated (Havaei, 2021;Liu et al, 2020;WHO 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Most research on workplace violence has conceptualized this phenomenon based on its types and sources of violence. In a 2003 report from the World Health Organization (Di Martino, 2003), workplace violence was classified into two broad categories: physical violence, which was described as the use of physical force leading to physical and psychological harm, and emotional violence, which refers to the use of nonphysical means leading to psychological harm (Havaei, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is because nurses provide 24-h direct patient care; they are, therefore, more likely to become the target of patient aggression and offensive behaviours (Royal College of Nursing, 2018). A systematic review on workplace aggression has estimated that between 7% and 83% of healthcare workers have been the target of violent acts (Piquero et al, 2013) and in particular, international evidence has estimated that 25%-67% of nurses are exposed to at least one type of workplace act of violence annually (Bahadir-Yilmaz & Kurşun, 2020;Havaei, 2021). A study conducted in 2000 found that 82% of US nurses had been assaulted at least once during their careers and 73% believed that assault was a part of their job (Watson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…WPV threatens, in fact, the well-being of both the workers and the organization they belong to, negatively influencing the rights of millions of people to work in a safe environment and affecting the organization with absenteeism and low productivity, among other things. For these reasons, worldwide, several international organizations [ 5 , 6 , 7 ], along with many different research groups [ 8 , 9 , 10 , 11 , 12 ], are underlining the importance of having specific guidelines to monitor and prevent the spreading of this phenomenon. In the last two decades, the number of scientific publications on this topic has grown.…”
Section: Introductionmentioning
confidence: 99%